2020
DOI: 10.7717/peerj.9796
|View full text |Cite
|
Sign up to set email alerts
|

CircHIPK3 regulates cardiac fibroblast proliferation, migration and phenotypic switching through the miR-152-3p/TGF-β2 axis under hypoxia

Abstract: Background The occurrence of pathological cardiac fibrosis is attributed to tissue hypoxia. Circular RNAs play significant regulatory roles in multiple cardiovascular diseases and are involved in the regulation of physiological and pathophysiological processes. CircHIPK3 has been identified as the one of the most crucial regulators in cardiac fibrosis. However, the mechanisms by which circHIPK3 regulates cardiac fibrosis under hypoxia remain unclear. Our study aimed to determine circHIPK3 expression in cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Similarly, another study showed circHIPK3 induced cardiac fibrosis through a circHIPK3/miR-29b-3p/Col1a1/Col3a1 signaling cascade in mouse diabetic cardiomyopathy model (86). Interestingly, circHIPK3 modulates CFs function in a hypoxia condition in a similar sponge manner, but through a different signaling cascade, the circHIPK3/miR-152-3p/TGF-β2 axis (87). Therefore, circHIPK3 is likely to be an important upstream node of the miRNA-mediated posttranscriptional gene regulation network in cardiac fibrosis.…”
Section: Circhipk3mentioning
confidence: 86%
“…Similarly, another study showed circHIPK3 induced cardiac fibrosis through a circHIPK3/miR-29b-3p/Col1a1/Col3a1 signaling cascade in mouse diabetic cardiomyopathy model (86). Interestingly, circHIPK3 modulates CFs function in a hypoxia condition in a similar sponge manner, but through a different signaling cascade, the circHIPK3/miR-152-3p/TGF-β2 axis (87). Therefore, circHIPK3 is likely to be an important upstream node of the miRNA-mediated posttranscriptional gene regulation network in cardiac fibrosis.…”
Section: Circhipk3mentioning
confidence: 86%
“…CircHIPK3 is widely expressed in various tissues, such as the heart, lung and colon ( 26 ), consistent with its roles in CVD ( 32 , 43 – 46 ), cancers ( 12 , 27 , 28 , 47 ), and neuronal diseases ( 48 , 49 ). CircHIPK3 mainly functions through sponging miRNAs ( 32 , 34 , 43 , 44 , 50 ). CircHIPK3 can be wrapped in exosomes to facilitate cell-to-cell communication ( 43 , 51 53 ).…”
Section: Biogenesis and Mechanisms Of Actions Of Circhipk3mentioning
confidence: 99%
“…Then, numerous non-beating myofibroblasts replace the functional myocardium, resulting in myocardial dysfunction ( 99 ). CircHIPK3 has been identified to be abundantly expressed in CFs and to function in myocardial fibrosis ( 34 , 44 ).…”
Section: Circhipk3 and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miR-152-3p targets CDK8 to regulate hepatic carcinogenesis [ 22 ]. CircHIPK3 sponges miR-152-3p to release TGF-β2, thus promoting cardiac fibrosis under hypoxia by regulating fibroblast proliferation and phenotypic switching [ 23 ]. Additionally, miR-152 regulates TCF-4 pathway in OA rats to weaken chondrocyte apoptosis and cartilage degeneration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%